Pengaruh Total Quality Management Dan Entrepreneurial Orientation Terhadap Organizational Performance Dimediasi Innovation - Maria Angelica Brigita, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to examine the influence of total quality management and entrepreneurial orientation toward organizational performance with a mediating effect study from innovation in Indonesian Sustainable Palm Oil certified palm oil agribusiness companies in Barito Timur and Kotawaringin Barat district. The sample was determined by quota sampling method. The research conducted by taking 8 palm oil agribusiness companies.Data processing techniques using partial least square method that helped by SmartPLS 3rd version. The result of this research shows that total quality management has not positively effect on organizational performance, total quality management has positively effect on innovation, innovation has positively effect on organizational performance, total quality management has positively effect on organizational performance mediated by innovation, and entrepreneurial orientation has positively effect on organizational performance